Efforts to Accelerate Stunting Reduction in Tegal City, Indonesia - Nilatul Izah; Yanyan Mulyani; Nina Maria Desi; Seventina Nurul Hidayah; Okta Zenita Siti Fatimah; Fitriana Rakhimah; Elqy Mei Zumaro; Resty Himma Muliani; Sa'adah Handayani; Satriya Pranata (Gonabad University of Medical Sciences, 2024)
Background: One of the problems currently faced by Indonesia is nutritional problems in the form of stunting. Stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, characterized by their length or height being below the standard.  Methods: This descriptive research aimed to describe the condition of stunting in Tegal City and the efforts of the Tegal City government in contributing to the reduction of the stunting rate.  Results: This activity has shown good results, this can be seen from the reduction in the stunting rate in Tegal City from 9.94% in 2022 to 8.21% in 2023. The program to reduce stunting rates in Tegal City was established through the formation of the stunting reduction acceleration team (SRAT). Some of the activities carried out by SRAT include sensitive services linked to poverty management program activities, such as providing integrated healthy livable houses, interventions in the use of yard land, expanding family planning acceptors, refining social assistance recipients, and providing access to drinking water and sanitation management. Specific services are carried out by strengthening specific interventions on a provincial scale, enhancing communication and behavior change by strengthening communication and behavior change and planning and monitoring the evaluation of regional apparatus organizations' program integration. Collaboration with potential partners is also key in accelerating stunting reduction, along with ongoing monitoring and evaluation of performance. This activity has shown positive outcomes, as evidenced by the reduction in the stunting rate in Tegal City from 9.94% in 2022 to 8.21% in 2023. Conclusion: The prevalence of stunted children in Tegal City has decreased. Effective leadership, a strong civil society, and targeting vulnerable communities during the implementation of specific and sensitive nutrition interventions are the main factors that support the achievement of these targets.